Highly sensitive photodetector based on ge double-barrier punch-through structure - O. A. Abdulkhaev; D. M. Yodgorova; A. V. Karimov; S. M. Kuliyev (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
In recent years, transmission and reception systems of optical signals are widely used. Receiving the optical signal in such systems is carried by photoreceiving modules based on a photodetector, which defines the quality of the received signal, the range and speed of the entire system. However, hitherto used p–i–n- and avalanche photodiodes do not fully meet the growing demands. The present work is devoted to investigate the photovoltaic characteristics of semiconductor thin base transistor structure based on germanium, which is superior the silicon counterparts by speed and gain. Investigated p+–n–p-structures were obtained by diffusion of antimony onto the substrate of p-type germanium to a depth of 1 µm and alloying of indium to the part of its surface which creates diffusion layer of p+-type and with thickness of 0,5 µm. Experiments have shown that the reverse biasing of a single p+–n-emitter-base junction leads to a smooth increase in reverse current, at the same time when it is connected in series to forward biased collector p–n-junction there is a sharp increase in the current by voltage, giving properties of voltage surge suppressor. This behaviour of the current-voltage characteristics can be explained by the punch-through effect when the space charge regions of the emitter junction and the space charge region of collector junction touch each other and the conditions are realized for double carrier injection into a fully depleted region of the transistor. At the same time giving small fixed voltages 0.1 – 0.15 V to the collector-base junction, the output static characteristics can be received with an operating voltage of 3.0 – 3.5 V. A characteristic feature of the investigated transistor is that when the base region under illumination by integrated light intensity (50 and 3000 lux) light current appears, whose magnitude with the increase of operating voltage (up to 1.7 V) increases nonlinearly, resulting in increased current photosensitivity up to 17 µA/lux, which is one and a half orders of magnitude greater than photosensitivity of germanium phototransistor “OOA-5”.